Analysis Of Transparency and Accountability In Local Government Management And Its Implications For Public Service Performance In West Sulawesi - Andriani Andriani; Muhammad Akbar S (Universitas Indonesia Membangun (Inaba), 2026)
This study explores the impact of transparency and accountability on local government management and their effects on public service performance in West Sulawesi Province, Indonesia. While transparency and accountability are widely discussed in public governance literature, there is limited empirical evidence on how local government management mediates these factors to enhance public service performance, particularly from the citizens' perspective. This research examines both the direct and indirect effects of transparency and accountability on public service performance through local government management. A quantitative approach was employed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) technique. Data were collected from 121 citizens who had interacted with local government services in West Sulawesi Province through a structured questionnaire with a five-point Likert scale. The analysis involved evaluating the measurement and structural models to assess construct validity, reliability, and proposed hypotheses. Findings indicate that transparency (β = 0.408, p < 0.001) and accountability (β = 0.321, p < 0.001) significantly enhance public service performance. Moreover, transparency (β = 0.472, p < 0.001) and accountability (β = 0.254, p = 0.001) significantly influence local government management, which in turn positively impacts public service performance (β = 0.340, p < 0.001). Local government management partially mediates the relationships between transparency, accountability, and public service performance. The structural model demonstrates substantial explanatory power with an R² value of 0.746, identifying transparency as the strongest predictor of both local government management and public service performance.